Tethered Venues: Discerning Distant Influences on a Field Site. (November 2019) - Menchik, Daniel A.
Ethnographers often study those who periodically meet to interact in multiple venues. This article focuses on how people who share and engage in tasks in recurrently visited venues define and change their social projects' problems and solutions. To address the complexities of this "meta-work, " I introduce the concept of "tethers." Tethers are links across venues that people use to set and shift these problems and solutions that are continuously being contested. Drawing on examples from the author's fieldwork and other ethnographic accounts of professional work, I examine three types of tethers: focal participants, things, and language. Paying attention to tethers also results in practical implications for managing subjects' use of the ethnographer as a tether, making decisions about what venues to observe, and developing strategies for focusing one's observations when in those venues. I argue that a focus on subjects' use of tethers across venues helps mitigate the challenges ethnographers face when accounting for the influence of temporally and geographically distant sites of recurrent interaction.